[PP.16.05] AORTIC STIFFNESS AGING IS INFLUENCED BY PAST PROFOUND IMMUNODEFICIENCY IN HIV-INFECTED INDIVIDUALS. (September 2016) - Boccara, F.; Maia-Leite, L.; Boyd, A.; Nuernberg, M.; Catez, E.; Lang, S.; Ederhy, S.; Haddour, N.; Girard, P.M.; Cohen, A.
Abstract : Objective: We aimed to evaluate the determinants of aortic stiffness progression in HIV-infected individuals. Design and method: A prospective study (2005–2015) was conducted in 91 HIV-infected individuals addressed in our cardiologic center. Aortic stiffness was assessed using carotid-femoral pulse wave velocity (cf-PWV) with the Complior® device. The change in cf-PWV during follow-up was modeled using simple and mixed-effect linear regression models. Differences in cf-PWV during follow-up were modeled between covariables (age, waist circumference, current smoking, diabetes, systolic blood pressure, heart rate, mean arterial pressure, hypertension, CD4+ T-cell nadir) in univariable and then in multivariable models using the forward-stewise procedure. The variables associated with cf-PWV in univariable analysis that had a P value < 0.20 were included in the final model. Results: Ninety-one HIV-infected individuals free of cardiovascular disease were included in this longitudinal study (mean follow up 7.6 years). At baseline, the mean age of the cohort was 47.8 ± 7.8 years (95% were male) and median duration of HIV infection was 14.1 (8.5–17.3) years and 88% of the patients were virologically suppressed. At follow up several of the clinical characteristics had changed. Specifically, there was an observed increase in body mass index 24.4 vs. 23.5 kg/m2 (<0.001), waist circumference (WC) 90 vs 86 cm (p < 0.001), and in the prevalence of hypertension (47% vs. 32%, p < 0.001) and dyslipidemia (63% vs. 45%, p < 0.001) and a decrease in active smoking (19% vs. 37%, p = 0.003). Mean first cf-PWV was 7.5 m/s (6.6–8.2) and the second 8.2 m/s (7.2–8.8) (p < 0.001), representing an annual absolute increase in cf-PWV of 0.10 m/s per year. Overall 46 patients (51%) had either an increase in cf-PWV or persisted with high cf-PWV after 7 years. In the final multivariable regression model the changes in cf-PWV over time were associated with age (p = 0.003), SBP (p = 0.002) and consistently with the CD4+ T-cell nadir at the first visit < 200/mm 3 (p = 0.002). Conclusions: Our results suggest that vascular aging in HIV-infected individuals is associated with past profound immunodeficiency, in combination with traditional risk factors like age and blood pressure.